Sociolegal Approaches - Meylikova Bokira Ilyoskhon kizi; Allanazarova Sitora Bakhtiyor kizi; Oymatova Dilorom Ro'zimurotovna (Euro Asian Journal Publishing, 2025)
This article presents the socio-legal reasons for the emergence of behavioral deviations, the types of crimes that arise from them. This approach, in turn, includes sociological and legal directions. Moral deviations are grouped on several grounds and information is provided about them. The degree and dynamics of deviation, various manifestations of the structure of learning, and the age-related factor determine the specificity of behavior at different stages of ontogenesis.
Keywords: sociology; legal; subject